The Education of a Modern International Manager - Maisonrouge, Jacques G. (Journal of International Business Studies, 1983)
This article is based upon a speech delivered by Mr. Jacques G. Maisonrouge, Senior Vice President, IBM Corporation, and Chairman of the Board, IBM World Trade Corporation, at the Annual Meeting of the Academy of International Business, Washington, DC, on 28 October 1982 when he became the first recipient of the International Business Leader of the Year award and was elected an Honorary Member of the Fellows of the Academy of International Business.